Mutter Erde. Über ein Motivgeflecht in der "Ästhetik des Widerstands" von Peter Weiss - Langer, Renate (Studia Germanica Posnaniensia, 2018)
This paper is an attempt to explain the ambivalent role of the mother in Peter Weiss's oeuvre. In his autobiographical novel Abschied von den Eltern he describes the "mythological years" of his childhood with a frightening mother and a warm-hearted nanny. Traces of these two unintegrable motherly objects can be found in most of Weiss's works. The mother's realm is the house whereas the nanny allows the child to discover the outside world. His first "exile" is the garden, where a sensual contact with nature is possible. The Earth becomes a place of refuge for Weiss's figures. But she is also men's grave: "Desire to return into the mother's womb = desire to die". Being the goddess of life and of death, the Earth herself is ambivalent. „Die Ästhetik des Widerstands” is full of symbols and mythological allusions referring to this. But they are to be seen in a historical and political context. The Earth is a victim of war, wounded by men's violence, and at the same time she represents the Utopian possibility of an existence in which mimetic empathy and sympathy replace aggression and destruction.